2019
DOI: 10.1111/mcn.12930
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of the composite index of anthropometric failure among children under 5 years old in Bangladesh

Abstract: The prevalence of stunting, wasting, and underweight are reported separately. However, the data of the multiple anthropometric failures combinations of these conventional indicators are scant. This study attempted to estimate the overall burden of undernutrition among children under 5 years old, using the composite index of anthropometric failure (CIAF), and to explore the correlates. The study used secondary data from the Bangladesh demographic and health surveys (BDHS), undertaken in 2014. CIAF provides an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
81
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(105 citation statements)
references
References 20 publications
20
81
4
Order By: Relevance
“…Our study found that children living in urban areas are less likely to experience anthropometric failure compared to rural children. This is consistent with previous studies conducted in Bangladesh [15] and Myanmar [26] and is most likely linked to better living conditions, and adequate all years-round food accessibility in urban areas. In addition, our ndings show that children from poorer households are at increased risk of anthropometric failure compared with children from richer households.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our study found that children living in urban areas are less likely to experience anthropometric failure compared to rural children. This is consistent with previous studies conducted in Bangladesh [15] and Myanmar [26] and is most likely linked to better living conditions, and adequate all years-round food accessibility in urban areas. In addition, our ndings show that children from poorer households are at increased risk of anthropometric failure compared with children from richer households.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, our ndings show that children from poorer households are at increased risk of anthropometric failure compared with children from richer households. This corresponds to many other studies done previously in developing countries like Ethiopia [17],Bangladesh [15] and India [33]. Pomati et al [34] analysed the data of several West and Central African countries found that the risk of anthropometric failure among children in wealthier households is half than that of the poorest households.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations